Fatigueless structures inspired by nature: A case study. Issue 3 (6th February 2019) - Berto, Filippo; Razavi, Javad
Abstract: Biomimetic has begun to offer significant potential in providing unique solutions in materials science. However, the full potential of mimicking natural systems can be fully exploited only if we start to look the problem of design of complex structures from the structural side. The present short letter is focused to investigate a simple case study to show the possibility of achieving an ideally fatigueless design inspired by nature. Materials cannot be immune from fatigue, but structures can. This case study is aimed to discuss a preliminary example.